Narrative moment. Musical performance according to Lawrence Kramer and James Baldwin - Szyszkowska, Małgorzata A. (Interdisciplinary Studies in Musicology, 2020)
My aims are to investigate how the concept of narrative moment may be helpful in capturing the role of music in creating profound communication on the level of performing as well as listening to musical performance. I aim to show how sharing a culminating moment in a musical experience may lead to inducing a state of self awareness and confidence in place of critical separation and distrust. I discuss Lawrence Kramer’s idea of the narrative moment explained in original in reference to a literary example and an improvised music. It is presented as an example of communicative potential in music performance, which as I argue, is worth exploring and explaining further. Suggesting a possibility of narrative moment in the experience of musical performances offers a comprehensible and applicable vision of communicative potential of music that is far reaching even if rarely achieved; a possibility of communication that is direct and intuitive, flexible and affective. Defining musical meaning in terms of its music’s communicative power and far reaching social consequences suggests deep connections between the social/intersubjective, individual/subjective and aesthetic aspects of life. The proper explanation of the meaning of music requires drawing from different domains, including metaphors and highly persuasive literary and musical examples.